Sistem pendukung keputusan pemilihan bimbingan belajar online bagi calon peserta SBMPTN menggunakan fuzzy topsis (studi kasus pada wilayah Blitar) - Septiana, Arneta Dwi Lola; Riski, Abduh; Kamsyakawuni, Ahmad (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2021)
Joint Selection of Higher Education State or SBMPTN is a route for admission of new students with fierce competition. One of the preparations carried out by students is to take part in online tutoring of the SBMPTN preparation learning program. This study aims to apply the TOPSIS fuzzy method in the selection of the SBMPTN preparation learning program. The criteria in this study are price, time, availability of tutors, facilities, rating on google play store, and promotion. The fuzzy approach and TOPSIS settlement steps are used to obtain the best ranking and alternatives. The methodologies of this research are calculating the decision matrix, calculating the normalized decision matrix, calculating the weighted decision matrix, determining the positive and negative ideal solutions, calculating the distance of each alternative to the ideal solution, calculating the relative proximity of each alternative, and ranking the final results. The final result of this study is a ranking of the SBMPTN preparation learning program in online tutoring institutions, which will be used as a decision-making tool. This decision support system helps prospective SBMPTN participants to choose a more objective learning program.